Pengaruh Environmental, Social, and Governance (ESG) disclosure terhadap kinerja keuangan dengan gender diversity sebagai variabel moderasi - Sari, Putri Sekar; Widiatmoko, Jacobus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study is to examine the effect of ESG Disclosure on financial performance. ESG disclosure provides a more complete picture of the sustainability aspects of corporate performance, which supports regulatory reporting in Indonesia. The research method uses quantitative methods with Moderated Regression Analysis (MRA). The results showed that ESG disclosure affects ROA. The better the quality of ESG disclosure can improve financial performance. It has not been proven that gender diversity has an influence on financial performance and moderates the relationship between ESG disclosure and ROA. The company's financial performance is negatively influenced by the control variables SIZE and LEV.